The active female. Health issues throughout the lifespan (Springer Nature, 2023)
Now in a revised and expanded third edition, the aims of The Active Female are threefold: first, to increase the awareness of wellness and fitness issues for active females and their family members; second, to provide an avenue for medical practitioners, allied health professionals, health educators/providers, and certified individuals in sports medicine/athletics to gain critical, updated knowledge of a field specific to active females; and third, to introduce the concept of obesity as a growing health concern even for normal weight individuals.